Antioxidant Activity Of Leaf Ethanol Extract And Balm Plant Sticks (Polygala paniculata L.) - Zidratil, Zidratil; Lestari, Wahyuni Dwi; Bibba, Yustina Massola; Darnayanti, Darnayanti; Islam, Fitri Nurul; Sukarti, Sukarti (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2024)
This research aims to determine the antioxidant activity of the leaves and stems of the balsam plant (Polygala paniculata Linn). The balsam plant (Polygala paniculata Linn) is a small shrub that grows wild and is utilized by the community in Bonelemo Village, Bajo Barat Sub District, Luwu Regency, South Sulawesi, as a traditional medicine for removing black spots on the face. One of the compounds contained in the balsam plant is flavonoids, which have the potential as antioxidants. The procedures carried out in this research include sample preparation, sample extraction using 96% ethanol solvent, macerate concentration, and subsequently conducting antioxidant activity tests using the DPPH method. The results of antioxidant activity testing of the leaves and stems of the balsam plant (Polygala paniculata Linn) obtained an IC50 value of 44,987 µg/mL. Based on this research, the leaves and stems of the balsam plant (Polygala paniculata Linn) are categorized as containing very strong antioxidant components.